Management of Nagari Pariangan Tourism Village and The Economic Impact of The Nagari Pariangan Community in Tanah Datar District, West Sumatra Province - Suci, Artha Mevia Eka; Yurisman; Septriani (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research discusses "Tourism Village Management and the Economic Impact of the Nagari Pariangan Community." The purpose of this research is to describe the management of the pariangan nagari tourism village and the economic impact of the pariangan community. The theory used in this research is the theory of community participation from Edward Inskeep.  The method used is a qualitative method with data collection techniques of observation, interviews and documentation. The findings in this study explain that the management and impact in this tourist village are by increasing human resources for all activists and tourism business actors in Nagari Pariangan, improving and developing tourism objects in Nagari Pariangan, and fostering ummkm in Nagari Pariangan. The impact of tourist villages on the community is an increase in community income through MSMEs and opening up new jobs.